2007
DOI: 10.21236/ada482276
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Transient Dynamics of Shock Wave Boundary Layer Interactions Using Hybrid Large-Eddy/Reynolds-Averaged Navier-Stokes Models

Abstract: Public Reporting burden for this collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing the collection of information. Send comment regarding this burden estimates or any other aspect of this collection of information, including suggestions for reducing this burden, to Washington Headquarters Services, Directorate for information Operations and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…NCSU's REACTMB-INS [24,25] solver is used for the computational fluid dynamics (CFD) calculations performed in this study. The governing equations are written in arbitrary Lagrangian/Eulerian form, which enables the motion of a body-fitted computational mesh in accord with prescribed rate laws.…”
Section: A Cfdmentioning
confidence: 99%
“…NCSU's REACTMB-INS [24,25] solver is used for the computational fluid dynamics (CFD) calculations performed in this study. The governing equations are written in arbitrary Lagrangian/Eulerian form, which enables the motion of a body-fitted computational mesh in accord with prescribed rate laws.…”
Section: A Cfdmentioning
confidence: 99%
“…To demonstrate this, several modeling and validation studies have been carried out. In the recent years, as a result of the improvement in computational facilities, the DNS, LES, or hybrid RANS modeling strategies are becoming attractive to capture the SWBLIs in canonical geometries like compression corner [16][17][18] and the pseudo-shock structure of normal SWBLIs in a duct. 19 Though, DNS/ LES studies have shown to capture the characteristics of SWBLIs quite accurately, it requires huge computational resources.…”
Section: Introductionmentioning
confidence: 99%